Workplace safety compliance of RMG industry in Bangladesh: Structural assessment of RMG factory buildings. (December 2015) - Ansary, Mehedi Ahmed; Barua, Uttama
Abstract: Ready-made garment (RMG) in Bangladesh faces challenges to ensure workplace safety for the millions of garment workers in compliance with the national and international labour standards and labour rights. The recent deadly Rana Plaza collapse resulted in three important plans of actions to address the challenges in the sector. This paper presents an assessment of the potential and challenges of RMG industry in Bangladesh. It presents a detail review of the initiatives taken after Rana Plaza accident along with progress made in terms of overcoming the challenges. It also presents a detail review of the actions the structural assessments of buildings housing RMG factories in Bangladesh including its progress, implementation mechanism, and outcomes. The study reveals that RMG is one of the most important export oriented business sector in Bangladesh, which has progressed a lot since the Rana Plaza collapse in terms of achieving workplace safety compliance under three plans of actions, among which achievement in initiatives regarding structural assessment of RMG factory buildings is significant. Still nearly 1000 factories remain to be assessed. Moreover, assessment of buildings is not an end in itself, based on the recommendations of the assessment, the weak factory buildings need to be made resilient by addressing the structural issues.